Sistem Pendeteksi Kebakaran dengan Arduino pada Gudang - Gideon Ekacipta Hutama; Agustinus Noertjahyana; Resmana Lim (Jurnal Infra, 2021)
Fire is undesirable but fire is unavoidable. Individually owned warehouses that are small to medium in size usually do not receive sufficient supervision. Therefore we need a smart system that can provide information to the owner about the state of the warehouse in real time so that the owner can receive notifications quickly in the event of a fire. Internet of Things as a platform where every tool is getting smarter, every process is smart, and communication is getting more informative every day. The Internet of Things through its development has provided us with many new technologies that enable tool-to-tool communication, as well as tool-to-human communication. From this technology allows us to create a suite of tools that function to monitor the warehouse for us and give us notifications in case of fire. From the tests conducted by the author, it can be seen that the level of smoke density that causes fires is around 5000PPM after being compared with similar products on the market. From the test it was also found that the average notification delay is 3.8 seconds which according to the ITU-TG.1010 standard is for delay (end to end <10s) so 3.8 is a good delay and meets these standards.